EFEKTIVITAS PENINGKATAN PENGETAHUAN KESEHATAN GIGI DAN MULUT MENGGUNAKAN MEDIA VIDEO DAN PERMAINAN ULAR TANGGA PADA SISWA SEKOLAH DASAR NEGERI CANDI 01 SEMARANG - Setiadi, Obed Kris; Yulianti, Natalia Ratna; Wahyuningrum, Eka; Nancy, Caecilia (Jurnal Perawat Indonesia, 2020)
Background: Dental caries is one of the serious health problems in school children. This put children on high risk of school achievement decreasing and lack of nutrition. It is important to provide them a health education which could be done by play program. There were two play programs proven as effective for health education namely snake ladder and watching video. However, little is known which program is more effective. This study aimed to investigate differences of increasing dental and mouth health knowledge using snake lader media and video. Methods: This study employed Pretest-Posttest nonequivalent control group design and  conducted in Candi 01 Elementary School, Semarang City. The sample of 74 people divided into 2 groups, 1 snake ladder group and 2 groups. Each group consisted of 37 people. Result: It was found that the snake ladder game was more effective in increasing health knowledge, in the Mann-Whitney alternative test the p value was 0.000 (p <0.005).Conclusion: There are differences in the benefits of health and oral knowledge using media videos and snake games on Candi 01 elementary school students in Semarang City.